Peningkatan Kesadaran Masyarakat akan Kebersihan Lingkungan dan Protokol Kesehatan di Desa Rukuramba Kabupaten Ende - Cahyani, Indri; Dadi, Agustinus F Paskalino; Mangu, Oktavianus O; Bolong, Josep Morison Y M; Wijaya, Maria N D (LPPM Universitas Flores, 2023)
Rukuramba Village is one of the villages in the Ende District. This village is located west of the city of Ende, with a distance of about 9 km and an arrival time of 10 minutes. As one of the villages located on the outskirts of Ende city, Rukuramba Village has several problems that need to be addressed and found solutions. The problems encountered in Rukuramba Village include 1). Public awareness is still low in maintaining environmental cleanliness. This can be seen in people who do not prepare trash cans in each residence, do not throw garbage in its place, and throw garbage in sewers and rivers. 2). There is no public awareness to carry out village environmental cleaning activities (conventional work) which are programmed together and regularly; 3). Most people have not obeyed health protocols specifically in terms of wearing masks. The solution offered in addressing this problem is to carry out activity 1). Environmental clean-up social service, 2). Installation of regional boundary signs and signs prohibiting waste disposal in certain areas, and 3). Distribution of masks to members of the public. This activity went smoothly and involved the community service implementation team with the villagers. The results achieved from this activity are the increasingly clean environment in the village, the awakening of public awareness to maintain environmental cleanliness, and having more than one mask so that it is possible to wear masks in a more orderly and orderly manner. With the awareness empowerment process carried out by the implementing team, it is hoped that the awareness to maintain environmental cleanliness in the community will continue to increase from time to time, and become more obedient to health protocols during the pandemic Covid-19.